Digitalisasi dan Keberlangsungan UMKM Kuliner Halal Selama Pandemi Covid-19 - Anton priyo nugrioho (Jurnal Ilmiah Ekonomi Islam, 2022)
The digitization of MSMEs is transforming the use of digital applications in micro, small and medium enterprises so that all forms of activity in them can be carried out through several applications that provide online buying and selling services, especially MSMEs in the culinary sector. This study determines the role of digitizing MSMEs on the sustainability of MSMEs in this Covid-19 pandemic condition due to changes in people's lifestyles that also impact the condition and sustainability of MSMEs. This qualitative research used interviews of 15 owners of culinary MSMEs labeled halal and 15 consumers around the Catur Tunggal sub-district, Depok Sleman. This study shows that the digitization of MSMEs plays a role in increasing the number of sales and business revenues and helps the sustainability of MSMEs during the Covid-19 pandemic